Etude contrastive français / anglais des anaphores lexicales dans la presse et dans la fiction littéraire - Emmanuel Baumer (Corela)
In this article, I tried to find out the similarities and the differences in the referential chains referring to a proper noun, according to textual genres (literary fiction / newspaper articles) and many other contextual parameters. When those referential chains in french and in english are compared, reccurring differences can be noticed, mainly as far as lexical anaphora are concerned.